2020
DOI: 10.21786/bbrc/13.8/157
|View full text |Cite
|
Sign up to set email alerts
|

Bone Bonding of Hafnium – A Literature Review

Abstract: Numerous biomaterials have been constantly researched upon for dental implants. We wanted to evaluate alternative elements that may have the potential to offer equivalent or superior osseointegration. One such element of interest is Hafnium. In the periodic table by IUPAC, tantalum belongs to period 6 (d block) of periodic table. Hafnium belongs to the same period and block as tantalum, in the periodic table. Various in vitro studies were conducted on hafnium metal. Studies have reported that hafnium has a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…The use of surface coatings to enhance the corrosion resistance of metallic implants has garnered significant interest in biomedical applications. The element, Hafnium, belongs to period 6 in the periodic table, similar to gold standard titanium [ 7 ]. In our previous study on rat mandibles, hafnium coating on endosseous implants showed equivalent osseointegration to titanium, the gold standard [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of surface coatings to enhance the corrosion resistance of metallic implants has garnered significant interest in biomedical applications. The element, Hafnium, belongs to period 6 in the periodic table, similar to gold standard titanium [ 7 ]. In our previous study on rat mandibles, hafnium coating on endosseous implants showed equivalent osseointegration to titanium, the gold standard [ 8 ].…”
Section: Introductionmentioning
confidence: 99%